2010
DOI: 10.1063/1.3271238
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical differential photoacoustic cell to study in situ the growing process of porous materials

Abstract: In order to study in situ the growing process of porous materials, a new electrochemical differential photoacoustic cell (DPC) was developed. This system allows to obtain the thermal signals coming from the growing process of the pores without the external noise component. The DPC is a good system to growth porous silicon and study their growing process with reproducibility. The porous silicon samples were obtained by using electrochemical etching of (100) n-type silicon wafers with different nominal resistivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…4, the change in the temperature of the sample is governed by the apparition of the porosity and changes in the thickness of the sample as shown in Eqs. (3) and (6). From a physics point of view, the reflectance during the etching process is periodic (see Figure 3 (a)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4, the change in the temperature of the sample is governed by the apparition of the porosity and changes in the thickness of the sample as shown in Eqs. (3) and (6). From a physics point of view, the reflectance during the etching process is periodic (see Figure 3 (a)).…”
Section: Resultsmentioning
confidence: 99%
“…The data reported by Gutierrez et al and Espinosa-Arbeláes et al showed an oscillatory character for the amplitude and phase signals of the photoacoustic signal. 6,7 This shows clearly that the photoacoustic signal depends on various parameters: substrate impurity concentration, current density, and the hydrofluoric acid (HF)/surfactant ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficients W n and U n are obtained from the temperature and the flux continuity for each AC component of Eqs. (10)- (12). It is easy to show that σ's are related to the thermal diffusivity α as follows:…”
Section: Photoacoustic Modelmentioning
confidence: 99%
“…PA has been used to study kinetic processes, thermal and electronic properties of semiconductor materials. [10][11][12][13] Therefore, it is expected that the PA technique could be able to detect in situ the chemical reaction and the changes in the optical properties during the PS formation.…”
Section: Introductionmentioning
confidence: 99%